Model Pembelajaran Pendidikan Agama Islam Tanpa Standar Kurikulum di Jazeeroh Phitayanusorn School Krabi Thailand - Ummu Salamah Simanullang; Mavianti Mavianti (Ta’dib : Jurnal Pendidikan Islam, 2025)
This study aims to describe the implementation of curriculum flexibility in Islamic Religious Education (PAI) learning at Jazeeroh Phitayanusorn School, Krabi, Thailand, as a minority Muslim community school. The study uses a qualitative approach with a case study method. The results of the study show that PAI learning is implemented by using the curriculum as a flexible guideline that is adapted to the teacher's abilities and the students' needs and characteristics. This flexibility provides teachers with autonomy in designing dialogical learning strategies, utilizing various learning resources, and using the school environment as an alternative learning space. Students show good involvement in behavioral, emotional, and cognitive dimensions. This finding provides a theoretical contribution by asserting that curriculum flexibility is a strategic approach in the development of Islamic education learning in the context of Muslim minorities, without relying on rigid national curriculum standards.